Association between Candida in Oral Submucous Fibrosis and Oral Lichen Planus - Ashok Vikey; Astha Pusame (Research Perspectives of Microbiology and Biotechnology Vol. 6, 2024)
Candida species are component of oral micro flora with prevalence of 3-70%, and are generally regarded as being commensals, hence probable role of candida in oral carcinogenesis cannot be excluded. Various microbiological studies suggest association of candida with potentially malignant lesions. Pathogenicity of candida depends on many factors such as; nutritional disorders, diabetes mellitus, long-term antibiotic or corticosteroid use, head and neck cancer, radiation therapy and HIV infections. Oral Submucous fibrosis (OSMF) is considered a as a high-risk precancerous condition that is associated with chewing areca nut. This is noticed that OSMF, patients show Candida colonization and further leading to malignant transformation. Similarly Oral Lichen Planus (OLP) is an autoimmune potentially malignant disorder. Recently researchers have noticed pathogenic microorganisms, such as Candida albicans in patients with oral lichen planus. Few studies have suggested that symptoms of Oral Lichen Planus may be exacerbated by candida overgrowth or infection. According to our findings; higher candida carriage revealed in OSMF+ OLP groups (23.3%); as compared to controls (10%). The species level findings showed 13.3% of candida albicans in OSMF+ OLP and6.7% in controls, candida krusei 6.7% in OSMF+ OLP and 3.3% in controls and non-candida albicans were 10% in OSMF+ OLP and 6.7% in control group respectively. Conclusion: The association of candida species with potentially malignant disorders such as OSMF and OLP aggravate to malignancies through secondary infections. So early assessment of these microbes in preliminary state of cancers can avoid further complications and help for better interventions.